Analisis Proses Produksi Dalam Perspektif Islam (Studi Kasus Home Industry Bakso Di Tembung) - Yusromuin Munthe; Dendi Dwi Putra Ritonga; Rizqa Amelia (Universitas 45 Surabaya, 2023)
In Islam, the concept of halal plays a central role in the lives of Muslims. Halal applies not only to food ingredients but also encompasses the entire process of food production and serving. In the context of meatball production, it is important to ensure that the ingredients used and the production processes align with Islamic principles. This includes the selection of halal ingredients, appropriate production methods, processing, storage, and handling of food that meet halal standards. In Islam, permissible animal meat must be slaughtered correctly, and additives such as seasonings and preservatives must be halal and free from haram substances. Additionally, ethical and fair treatment of workers is also considered. In Indonesia, efforts have been made to ensure that meatball production aligns with Islamic principles, and halal certification bodies have been established. The Islamic approach to meatball production can provide confidence to Muslim consumers and build a good relationship between producers and consumers. This approach can also serve as an example for the entire food industry to ensure halal and high ethical standards in food production. In this study, a qualitative method was used to understand the community's experience related to tembung meatballs. The results of this research highlight the importance of halal meatball product management, good human resource management, and quality control in halal meatball production in Tembung